MON-208 Age-Dependent Progression of Renal Dysfunction After Adrenalectomy for Aldosterone-Producing Adenomas in Japan - Yoshioka, Masayuki (J Endocr Soc, 2020)
Context: In patients with aldosterone-producing adenomas (APAs), adrenalectomy causes a rapid decrease in blood pressure and increase in blood potassium levels; however, the effects of these intensive metabolic changes on kidney function with age have not yet been examined in Japan. Objective: To investigate factors related to the progression of kidney dysfunction after adrenalectomy in different age groups. Participants: Fifty Japanese patients with APAs with 27,572 health check-up subjects as controls were examined. Main Outcome Measures: We investigated changes in eGFR after adrenalectomy and characterized patients who progressed to chronic kidney disease (CKD).Results: Receiver Operating Characteristic and multivariate analyses revealed the postoperative cut-off age of CKD to be 50 years (sensitivity, 57%; specificity; 82%; AUC, 0.69) and identified age as a unique factor for the progression of CKD after adrenalectomy. Among preoperative patients with APAs, CKD was 6% for those younger than 50 years (<50) and 40% for those 50 years and older (≥50). As a control, in 27,572 health check-up subjects, the prevalence of CKD was 4.2% in men and 2.5% in women aged 41-50 years and 18.9% in men and 13.3% in women older than 61 years, clearly demonstrating the higher prevalence of CKD in patients with APAs than in healthy subjects, particularly those with APAs ≥50 years. In patients with APAs <50 years, median eGFR before and after adrenalectomy were 95 mL/min/1.73m(2) and 88 mL/min/1.73m(2), respectively, indicating that the percentage of the decrease in eGFR was -7%, which was not significant (paired t-test, p=0.13). In contrast, in patients with APAs ≥50 years, median eGFR after adrenalectomy decreased to 42 mL/min/1.73m(2) from 67 mL/min/1.73m(2) (adjusted by age, paired t-test, p=0.01) (percent decrease in eGFR, -24%) Patients with APAs ≥50 years who progressed to CKD showed higher preoperative aldosterone/renin ratios, lower potassium and chloride levels, lower BMI, and a higher incidence of a history of cardiovascular events and KCNJ5 mutation rates.Conclusion: Age is the most important predictor of the progression of kidney dysfunction after adrenalectomy in Japanese patients with APAs, particularly those with a history of cardiovascular events and positivity for KCNJ5 mutations.